There's No Place Like Home: The Profitability Gap between Headquarters and their Foreign Subsidiaries - Matthias Dischinger; Nadine Riedel (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2009)
Using a large panel data set for European firms, this paper provides evidence that operations at multinational headquarters are significantly more profitable than perations at their foreign subsidiaries. The effect turns out to be robust and quantitatively large. Our findings suggest that the profitability gap is partly driven by agency costs which arise if value-driving functions are managed by a subsidiary that is geographically separated from the headquarters management. In line with falling communication and travel costs over the last decade, the profitability gap is shown to decline over time. Apart from that, our results indicate that a higher competitiveness of multinational firms in their home markets also contributes to the profitability gap. We discuss various implications of our findings.
urn:nbn:de:bvb:19-epub-10976-0
Keywords: L25; D82; F23; H25; 330; profitability distribution; multinational enterprise; corporate taxes; Multinationales Unternehmen; Auslandsinvestition; Unternehmenszentrale; Tochtergesellschaft; Ausländische Tochtergesellschaft; Rentabilität; Europa